2017
DOI: 10.1002/ejsp.2219
|View full text |Cite
|
Sign up to set email alerts
|

The moral contents of anti‐atheist prejudice (and why atheists should care about it)

Abstract: Anti‐atheist prejudice is pervasive worldwide. Past research indicates that this is driven by perceptions of atheist immorality, yet such perceptions have not been explored in detail. Using Moral Foundations Theory and samples of U.S. Christians, we investigated whether anti‐atheist prejudice is explained by atheists' perceived adherence to certain foundational moral values more than others. Study 1 participants completed measures of moral value endorsements from the perspective of a typical atheist. Study 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Study 1 provides initial evidence that informational manipulations such as the inclusion of secular policy statements can increase voter support for atheist political candidates, perhaps in large part due to concurrent increases in perceptions that the target candidate was honest and trustworthy. This interpretation of the results is consistent with the secular morality hypothesis as well as the findings of Simpson and Rios (2016b), who showed that anti-atheist prejudice was more pronounced among those perceiving atheists to lack a moral concern for the welfare of others. While Study 1 offers encouragement for groups and individuals who wish to increase support for atheist candidates, these results are not without qualification.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Study 1 provides initial evidence that informational manipulations such as the inclusion of secular policy statements can increase voter support for atheist political candidates, perhaps in large part due to concurrent increases in perceptions that the target candidate was honest and trustworthy. This interpretation of the results is consistent with the secular morality hypothesis as well as the findings of Simpson and Rios (2016b), who showed that anti-atheist prejudice was more pronounced among those perceiving atheists to lack a moral concern for the welfare of others. While Study 1 offers encouragement for groups and individuals who wish to increase support for atheist candidates, these results are not without qualification.…”
Section: Discussionsupporting
confidence: 91%
“…Because a perceived lack of morality may be motivating distrust and prejudicial attitudes toward atheists, one way to increase political acceptance of an atheist candidate among religiously affiliated voters may be for a candidate to express broadly popular secular moral values. The degree to which an individual perceives atheists to have a moral concern for the welfare of others was found to be especially predictive of anti-atheist prejudice (Simpson and Rios 2016b). Study 1 tests the hypothesis that an atheist political candidate would receive a boost in voting intentions, trustworthiness ratings, and morality ratings from participants when the candidate expressed policy positions reflecting popular secular moral values.…”
Section: Factors Underlying Anti-atheist Prejudicementioning
confidence: 99%
“…Indeed, atheists' experiences might very well produce struggles in these areas, especially where atheists are a minority. Regarding interpersonal struggles, studies using U.S. participants have found that atheists are consistently rated as immoral (e.g., Gervais 2014), uncaring (Simpson and Rios 2017), and even un-American (Edgell et al 2006;Edgell et al 2016). These attitudes may lead to anti-atheist behavior, as many atheists report experiences of anti-atheist discrimination (e.g., Brewster et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate similar findings of atheists being the most frequently thought to violate moral foundations (Gervais, ). Although Christians consider atheists less likely to endorse moral foundations, perceptions of how caring, kind, and compassionate atheists are significantly predict prejudice towards them (Simpson & Rios, ). Atheists could thus be considered threatening not simply to an individual, but threatening the loyalty, authority, and sanctity foundational to closely knit moral communities (Graham & Haidt, ).…”
Section: …And Why?mentioning
confidence: 99%